Worship, community and the triune God of grace - Torrance, James B.; Didsbury lectures, 1994. (Carlisle, UK Paternoster, 1996)
Includes bibliographical references.
The Didsbury lectures are delivered annually at the Nazarene Theological College, Manchester, by leading scholars from a variety of schools of thought.
Keywords: Worship